The ability of TRIM3 to induce growth arrest depends on RING-dependent E3 ligase activity - Raheja, Radhika (Biochem J, 2014)
Mutation of the TRIM (tripartite motif)-NHL family members brat and mei-P26 perturb the differentiation of transit-amplifying progenitor cells resulting in tumour-like phenotypes. The NHL (named after the NCL1, HT2A and LIN41 repeat) domain is essential for their growth suppressive activity, and they can induce cell-cycle exit in a RING-independent manner. TRIM3 is the only bona fide tumour suppressor in the mammalian TRIM-NHL subfamily and similar to the other members of this family, its ability to inhibit cell proliferation depends on the NHL domain. However, whether the RING domain was required for TRIM3-dependent cell-cycle exit had not been investigated. In the present study, we establish that the RING domain is required for TRIM3-induced growth suppression. Furthermore, we show that this domain is necessary to promote ubiquitination of p21 in a reconstituted in vitro system where UbcH5a is the preferred E2. Thus the ability of TRIM3 to suppress growth is associated with its ability to ubiquitinate proteins.